Ageing, Technology and Home Care - Maggie Mort, Christine Milligan, Celia Roberts, Ingunn Moser (dir.) (Presses des Mines, 2008)
This book focuses on home as a site of care, with new technologies and for elderly population. It pulls together findings from research in the social sciences and common knowledge of the actors themselves, especially stakeholders involved in the design, delivery and receipt of 'care in place'. It offers a wide-ranging discussion of key issues raised in both the academic and grey literature in relation to new technologies and responsibilities for health care at home. Then, it identifies critic...